Delivery and outcomes of end‐of‐life care in the Australian context: Experiences and reflections of general practitioners. (2nd August 2022) - Ding, Jinfeng; Licqurish, Sharon; Cook, Angus; Ritson, Dianne; Masarei, Carolyn; Chua, David; Mitchell, Geoffrey; Johnson, Claire E.
Abstract: Previous research on general practitioners' (GPs') involvement in end‐of‐life care has largely focused on a specific aspect of care or has provided broad overviews that failed to capture individual variations in patient management. This qualitative study aimed to explore Australian GPs' feedback and reflections on the individual‐level care provided for patients in their last year of life. The findings of the study were drawn from a nation‐wide survey of GPs' experiences in end‐of‐life care. We analysed responses from 63 GPs for 267 of the 272 reported deaths. Factors influencing delivery of optimal end‐of‐life care reported by GPs were categorised into four groups: patient‐related factors, carer‐related factors, interactions between GPs and patients/carer‐related factors and broader health system issues. Each group included both barriers and facilitators. Our study highlighted importance of the emotional dimensions of therapeutic relationships with patients and their family, availability and capacity of family support and smooth communication and continuity of care between GPs and hospitals in delivery of optimal end‐of‐life care. Lack of these facilitators, misconceptions of palliative care and conflicts on implementing care plans among patients and their family tended to impede delivery of such care. On the basis of our findings in the present study and previous literature, we conclude that improved end‐of‐life care in general practice requires comprehensive approaches to supporting both the GP and family to provide care in patients' preferred place, such as enhanced palliative care training and improved availability of external support for GPs, higher levels of hospital‐based services reaching into community settings and broader community‐based resources for families beyond simply the healthcare system.